KEBEBASAN AKADEMIK DAN OTONOMI KEILMUAN DALAM SISTEM PEMERINTAHAN DEMOKRASI PANCASILA (Studi Kasus Webinar Constitutional Law Society Fakultas Hukum Universitas Gadjah Mada Yogyakarta) - Delpedro Marhaen Rismansyah; Tundjung Herning Sitabuana (Fakultas Hukum Universitas Tarumanagara, 2022)
Academic freedom and scientific autonomy are rights held by students and professors, butacademic freedom and scientific autonomy often experience problems such as those in thewebinar Case Study,